Parametric Design of Roller Chain Sprocket based on SINOVATION7. 0 - Zhu Zhuoyue; Xu Zhigang; Shen Weidong; Yang Deyu (Jixie chuandong)
According to the design criterion of roller chain sprocket,the parametric design of roller chain sprocket is completed based on SINOVATION7. 0. The users can set the parameter values according to the roller chain sprocket type,row number,tooth number and other basic parameters,then the chain wheel designer can be compiled to create the 3D model and calculate the strength and of the sprocket. It not only can output report for HTML,but also can export as CAD graphics and be assembled. With the help of the parametric design of roller chain sprocket,the design efficiency is improved and the cost is saved.